Impacts of Social and Emotional Learning Interventions for Teachers on Teachers' Outcomes: A Systematic Review With Meta-Analysis - Oliveira, Sofia; Roberto, Magda Sofia; Pereira, Nádia Salgado; Marques-Pinto, Alexandra; Veiga-Simão, Ana Margarida (Frontiers in Psychology, 2021)
Teaching is among the most emotionally demanding jobs, impacting teachers’ personal lives and job performance. Since teaching-specific stressors are mainly socio-emotional related, social and emotional learning (SEL) interventions targeting teachers have increased rapidly in recent years. This study conducted a systematic review with meta-analysis of 43 empirical studies which evaluated the efficacy of school-based SEL interventions involving 3,004 in-service teachers. The initial systematic review showed that these interventions were very heterogeneous and the research on their efficacy assessed widely distinct outcome variables. Concerning the meta-analysis, results showed statistically significant small to medium effect sizes favoring the experimental group, with SEL interventions impacting teachers’ social and emotional competence (g = 0.59, 95% CI [0.29, 0.90]), well-being (g = 0.35, 95% CI [0.16, 0.54]), and psychological distress (g = -0.34, 95% CI [-0.57, -0.10]). Meta-regressions did not reveal significant values of the explanatory variables, and publication bias was found for social and emotional competence and well-being domains. Findings add to growing empirical evidence regarding the impact of these interventions and contribute to the development of guidelines for the design of effective SEL interventions for teachers